Recursos tecnológicos y su incidencia en el rendimiento académico de los estudiantes de séptimo año de educación básico de la unidad educativa padre Cayetano Tarruell en la ciudad de Guayaquil en el año 2016 - Freire Vilema, Yadira Maribel (2016)
Resources and their impact on academic performance, as elements of measurement and description of the environment in which the educational process of the seventh year students of basic education of the Unidad Educativa "Padre Cayetano Tarruell" located in the city of Guayaquil. In the development of the research were used the methods: analytical, synthetic, statistical, inductive and deductive; Corresponded to the techniques of bibliographic research and field research such as: observation, survey, interview, reading and graphic organizers……